Mutations in AP3D1 associated with immunodeficiency and seizures define a new type of Hermansky-Pudlak syndrome. - Ammann, Sandra; Schulz, Ansgar; Krägeloh-Mann, Ingeborg; Dieckmann, Nele MG; Niethammer, Klaus; Fuchs, Sebastian; Eckl, Katja Martina; Plank, Roswitha; Werner, Roland; Altmüller, Janine; Thiele, Holger; Nürnberg, Peter; et al. (American Society of Hematology, 2016)
Genetic disorders affecting biogenesis and transport of lysosome-related organelles are heterogeneous diseases frequently associated with albinism. We studied a patient with albinism, neutropenia, immunodeficiency, neurodevelopmental delay, generalized seizures, and impaired hearing but with no mutation in genes so far associated with albinism and immunodeficiency. Whole exome sequencing identified a homozygous mutation in AP3D1 that leads to destabilization of the adaptor protein 3 (AP3) complex. AP3 complex formation and the degranulation defect in patient T cells were restored by retroviral reconstitution. A previously described hypopigmented mouse mutant with an Ap3d1 null mutation (mocha strain) shares the neurologic phenotype with our patient and shows a platelet storage pool deficiency characteristic of Hermansky-Pudlak syndrome (HPS) that was not studied in our patient because of a lack of bleeding. HPS2 caused by mutations in AP3B1A leads to a highly overlapping phenotype without the neurologic symptoms. The AP3 complex exists in a ubiquitous and a neuronal form. AP3D1 codes for the AP3δ subunit of the complex, which is essential for both forms. In contrast, the AP3β3A subunit, affected in HPS2 patients, is substituted by AP3β3B in the neuron-specific heterotetramer. AP3δ deficiency thus causes a severe neurologic disorder with immunodeficiency and albinism that we propose to classify as HPS10.
Keywords: Adaptor Protein Complex 3; Adaptor Protein Complex delta Subunits; Electrophoresis, Polyacrylamide Gel; Fluorescent Antibody Technique; Hermanski-Pudlak Syndrome; Humans; Immunologic Deficiency Syndromes; Mutation; Seizures; Transfection